Effects of plyometric and sprint training on physical and technical skill performance in adolescent soccer players - Saez de Villarreal, E.; Suarez-Arrones, L.; Requena, B.; Haff, G. G.; Ferrete, C. (The Journal of Strength and Conditioning Research, 2015)
To determine the influence of a short-term combined plyometric and sprint training (9 weeks) within regular soccer practice on explosive and technical actions of pubertal soccer players during the in-season. Twenty-six players were randomly assigned to 2 groups: control group (CG) (soccer training only) and combined group (CombG) (plyometric + acceleration + dribbling + shooting). All players trained soccer 4 times per week and the experimental groups supplemented the soccer training with a proposed plyometric-sprint training program for 40 minutes (2 days per weeks). Ten-meter sprint, 10-m agility with and without ball, CMJ and Abalakov vertical jump, ball-shooting speed, and Yo-Yo intermittent endurance test were measured before and after training. The experimental group followed a 9-week plyometric and sprint program (i.e., jumping, hurdling, bouncing, skipping, and footwork) implemented before the soccer training. Baseline-training results showed no significant differences between the groups in any of the variables tested. No improvement was found in the CG; however, meaningful improvement was found in all variables in the experimental group: CMJ (effect size [ES] = 0.9), Abalakov vertical jump (ES = 1.3), 10-m sprint (ES = 0.7-0.9), 10-m agility (ES = 0.8-1.2), and ball-shooting speed (ES = 0.7-0.8). A specific combined plyometric and sprint training within regular soccer practice improved explosive actions compared with conventional soccer training only. Therefore, the short-term combined program had a beneficial impact on explosive actions, such as sprinting, change of direction, jumping, and ball-shooting speed which are important determinants of match-winning actions in soccer performance. Therefore, we propose modifications to current training methodology for pubertal soccer players to include combined plyometric and speed training for athlete preparation in this sport.